2011
DOI: 10.1515/hf.2011.042
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental variation in heartwood colour of Australian blackwood (Acacia melanoxylon R.Br.)

Abstract: Australian blackwood (Acacia melanoxylon R.Br.) is a highquality appearance-grade timber species native to eastern Australia. It is characterised by dark-coloured heartwood, with colour varying from pale straw to red-brown and walnut brown, and pale cream-coloured sapwood. This wide range in heartwood colour is expressed as between-and within-tree variation, and is regarded as a problem in markets where colour consistency is important. To understand the genetic and environmental control of heartwood colour, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Significant trial, seedlot and interaction effects on all mean heartwood colour traits were found (Table 1), consistent with the results of Bradbury et al (2011) where individual colour measures were analysed using a mixed model which fitted a cubic spline to model within-core variation. The significant trial effect was due to the heartwood from the nurse crop trial Virginstow (266/4/1) being lighter, less red and less yellow than the heartwood from the other trials (Table 3).…”
Section: Heartwood Coloursupporting
confidence: 84%
See 1 more Smart Citation
“…Significant trial, seedlot and interaction effects on all mean heartwood colour traits were found (Table 1), consistent with the results of Bradbury et al (2011) where individual colour measures were analysed using a mixed model which fitted a cubic spline to model within-core variation. The significant trial effect was due to the heartwood from the nurse crop trial Virginstow (266/4/1) being lighter, less red and less yellow than the heartwood from the other trials (Table 3).…”
Section: Heartwood Coloursupporting
confidence: 84%
“…The significant trial, seedlot and interaction effects for all heartwood colour traits have been reported previously using different analyses (Bradbury et al 2011) and demonstrate the complex nature of heartwood colour expression in blackwood. Mean and maximum measures of within-core variation (ΔE) showed no significant seedlot or trial effects, despite the significant effect of trial and seedlot on the linear change in heartwood colour reported previously (Bradbury et al 2011). This suggests this methodology may have little power to detect biologically significant differences in within-tree colour variation.…”
Section: Genetic and Environmental Variation In Wood Propertiessupporting
confidence: 71%
“…Heartwood colour has been found to be under genetic control in Eucalyptus dunnii Maiden (Vanclay et al 2008) and Acacia melanoxylon R.Br. (Bradbury et al 2011), with some genetic control of within-tree colour variation (Bradbury et al 2011). Environmental factors have also been found to affect heartwood colour in Acacia melanoxylon (Bradbury et al 2011) and Juglans nigra L. (Rink 1987), and to interact with the genetic control of heartwood colour in Acacia melanoxylon (Bradbury et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(Bradbury et al 2011), with some genetic control of within-tree colour variation (Bradbury et al 2011). Environmental factors have also been found to affect heartwood colour in Acacia melanoxylon (Bradbury et al 2011) and Juglans nigra L. (Rink 1987), and to interact with the genetic control of heartwood colour in Acacia melanoxylon (Bradbury et al 2011). While the North Island forest sites had no noticeable effect on the heartwood a* colour of the coast redwood trees, the selection of clones for heartwood colour may require testing for the expression of heartwood colour in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate cutting angle and the observation of the differences in longitudinal and radial position of eucalypt clones are recommended for more homogeneity based on the final colour desired (Mori et al 2005). Colour variation within a species is frequent and can be related to genetic and environmental characteristics (Bradbury et al 2011). Significant difference in the L*a*b* values between species, provenances and sites as well as between young trees from plantations and old trees from natural stands was described by Gierlinger et al (2004).…”
Section: Colorimetrymentioning
confidence: 99%